Lutando pela terra e fazendo o morador : identidade e território em uma vila pesqueira - Pereira, Ana Luísa Lisboa Nobre (2017)
This research aims to analyze the identity emergence process and the construction of the territory of a fishermen community located at the east coast of the State do Ceará, the Vila do Estevão. For that matter, I have focused in the field of practical-discursive relations on the differences in the center of which situated agents symbolically appropriate themselves of speeches and normative categories, creating an autonomous political field that works as an intermediate instance where the politically organized community organizes their responses. After successive interventions from the State through administrative acts related to the territory, the local residents association had a part of the territory permanently titled. However, the existence of a clause and the way that the public agency conducted the titling led the residents to understand that the title would be valid for ten years and might be renewed if the contractual conditions were fulfilled. For one decade, the local residents association sought to build a good reputation with the public agency through the demonstration of commitment. Thus, has regulated the attribution of the right to a land lot as an internal administrative process and selected among the ways of constituting familiar relationships and the manners of managing the territory those that could serve to the formation of a native recognizing policy. A clause has became applied to residents their own, who should participate in the local residents association’s mobilizations for one year, after which it is hoped that the bureaucracy could have contributed to institute new modes of belonging and produced specific territorialities oriented to the fight for land.